Managing disaster risk in emerging economies - Kreimer, Alcira; Arnold, Margaret, 1965- (Washington, D.C. : World Bank, 2000)
The book focused on events on creating strategic partnerships to reduce the impacts of disaster on developing countries.
Includes bibliographical references.
uaj 04/05/2015
Loan
Keywords: Emergency management -- Economic aspects -- Developing countries; Emergency management -- Developing countries; Disaster relief -- Economic aspects -- Developing countries